Modelling and control of an omnidirectional mobile manipulator - Djebrani, Salima; Benali, Abderraouf; Abdessemed, Foudil (Zielona Góra: Uniwersytet Zielonogórski)
A new approach to control an omnidirectional mobile manipulator is developed. The robot is considered to be an individual agent aimed at performing robotic tasks described in terms of a displacement and a force interaction with the environment. A reactive architecture and impedance control are used to ensure reliable task execution in response to environment stimuli. The mechanical structure of our holonomic mobile manipulator is built of two joint manipulators mounted on a holonomic vehicle.
Keywords: holonome mobile manipulators; input state linearization; virtual impedance control; fuzzy logic